Fifty Years of Killing and Letting Die: On the Limits of Philosophical Bioethics - Räsänen, Joona (Bioethics, 2026)
In 1975, The New England Journal of Medicine published James Rachels' article ‘Active and Passive Euthanasia’. The argumentative method that Rachels introduced, the Bare Difference Argument (also known as the Contrast Strategy), became one of the most widely used tools in ethical reasoning. The argument, however, fails to show active euthanasia being morally permissible. It fails because Rachels takes the intuitions from the case where letting die is morally impermissible and applies the intuitions to cases where letting die is morally permissible. While it is possible to create thought-experiments that are more analogous to euthanasia, in this respect, than Rachels' cases, they too are disanalogous to euthanasia with some of the relevant features. Creating the perfect analogy, however, would be a mistake too. Such a case would be too analogous; people would simply be divided on what kind of moral intuitions they would have. The problem thus highlights a methodological limit in philosophical bioethics and raises questions related to the roles of philosophical ethicists in the context of assisted dying.